2022
DOI: 10.3390/nu14061140
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oral Creatine Supplementation on Power Output during Repeated Treadmill Sprinting

Abstract: The aim of the present study was to examine the effects of creatine (Cr) supplementation on power output during repeated sprints on a non-motorized treadmill. Sixteen recreationally active males volunteered for this study (age 25.5 ± 4.8 y, height 179 ± 5 cm, body mass 74.8 ± 6.8 kg). All participants received placebo supplementation (75 mg of glucose·kg−1·day−1) for 5 days and then performed a baseline repeated sprints test (6 × 10 s sprints on a non-motorised treadmill). Thereafter, they were randomly assign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 65 publications
2
9
1
5
Order By: Relevance
“…Furthermore, although in Set 3 there was no statistical significance, the CR group performed 12.7% more repetitions. These results are in line with those of previous studies, which consistently report that CR supplementation increases the capacity to recover between peaks of intermittent activity during different types of exercise, such as repeated Wingate efforts [ 26 , 47 ], rowing sprints [ 48 ], cycling sprints [ 14 , 24 , 25 , 49 ], running sprints [ 28 , 29 , 30 , 31 ], swimming sprints [ 32 ], resistance exercise [ 33 , 34 , 47 ], and maximal voluntary isokinetic contractions [ 15 ]. This could be due to the increase in the content of intramuscular PCr produced by the CR supplementation, since increases of 10–40% in the content of PCr have been previously reported [ 6 ], as well as increases in the amount of PCr re-synthesis during the different recovery periods [ 50 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, although in Set 3 there was no statistical significance, the CR group performed 12.7% more repetitions. These results are in line with those of previous studies, which consistently report that CR supplementation increases the capacity to recover between peaks of intermittent activity during different types of exercise, such as repeated Wingate efforts [ 26 , 47 ], rowing sprints [ 48 ], cycling sprints [ 14 , 24 , 25 , 49 ], running sprints [ 28 , 29 , 30 , 31 ], swimming sprints [ 32 ], resistance exercise [ 33 , 34 , 47 ], and maximal voluntary isokinetic contractions [ 15 ]. This could be due to the increase in the content of intramuscular PCr produced by the CR supplementation, since increases of 10–40% in the content of PCr have been previously reported [ 6 ], as well as increases in the amount of PCr re-synthesis during the different recovery periods [ 50 ].…”
Section: Discussionsupporting
confidence: 92%
“…This could indicate that subjects who were supplemented with CR, despite them having performed more mechanical work, obtained a similar value of metabolic stress. Previous studies report similar results, with constant blood lactate and pH values, suggesting that anaerobic glycolysis is not altered by CR supplementation [ 31 ]. On the same vein, other studies have shown that CR supplementation did not alter the blood lactate concentrations after 3.5 min of recovery following intermittent sprints in soccer players [ 29 ], nor immediately or one hour after performing 6 35 m sprints at a maximum speed with 10 s of recovery between the sprints [ 30 ].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…İskelet kaslarındaki kreatin miktarının optimal düzeyde olması yüksek miktarda fosfokreatin depolarına katkı sağlamaktadır. Bu durum yapılan egzersizin şiddeti ile birlikte ATP (Adenozin trifosfat) hidrolizi hızının belirlenmesine katkı sağladığından önem arz etmektedir [1,3,5,20,[29][30][31][32][33].…”
Section: Kreatinunclassified
“…Kreatin takviyesi, kısa süreli, yüksek yoğunluklu egzersizlerde, güç ve etkinliğin yanı sıra yağsız vücut kütlesini de artırmaktadır. Bu özelliği nedeniyle en yüksek kullanımın güreşçiler tarafından olduğu bilinmektedir [1,20,[29][30][31][32][33].…”
Section: Kreatinunclassified